2002
DOI: 10.1093/jac/dkg007
|View full text |Cite
|
Sign up to set email alerts
|

Early administration of oral oseltamivir increases the benefits of influenza treatment

Abstract: Our objective was to evaluate the benefit of early treatment of influenza illness using oral oseltamivir. This open-label, multicentre international study investigated the relationship between the interval from illness onset to first dose (time-to-treatment) and illness duration in the intent-to-treat infected population using accelerated failure time (AFT) modelling. A total of 1426 patients (12-70 years) presenting within 48 h of the onset of influenza symptoms were treated with oseltamivir 75 mg twice a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
262
2
11

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(293 citation statements)
references
References 19 publications
17
262
2
11
Order By: Relevance
“…Recent clinical observations of kinetics of influenza A infection in humans reveal that these viruses rapidly replicate to high levels of viral titres and deplete the pool of target cells before an effective immune response can be launched (Baccam et al 2006). While early treatment (within 48 hours of the onset of clinical symptoms) appears to be critical in influenza infection control (Aoki et al 2003), it poses a major concern for the emergence and spread of drug resistance in the population that should be addressed by assessing the probable epidemiological outcomes of different treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinical observations of kinetics of influenza A infection in humans reveal that these viruses rapidly replicate to high levels of viral titres and deplete the pool of target cells before an effective immune response can be launched (Baccam et al 2006). While early treatment (within 48 hours of the onset of clinical symptoms) appears to be critical in influenza infection control (Aoki et al 2003), it poses a major concern for the emergence and spread of drug resistance in the population that should be addressed by assessing the probable epidemiological outcomes of different treatment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that inhibition of influenza virus replication as early as possible via administration of antiviral therapy reduces the duration and severity of illness (5). Another recent report also suggested that delayed presentation and initiation of antiviral therapy are responsible partly for some deaths (6).…”
Section: Case Reportmentioning
confidence: 99%
“…A key difference between pre‐pandemic distribution of antivirals and pre‐dispensing just prior to or in the middle of a wave of pandemic influenza is that the time frame for wastage is much shorter in the present case. Thus, we expect that B will primarily reflect the advantage of early versus delayed treatment, for which there is some evidence 1 , 2 , 3 , 4 , 5 …”
Section: Risks Of Pre‐dispensingmentioning
confidence: 99%
“…The ability of antiviral drugs to alleviate symptoms and shorten their duration is well documented for seasonal influenza, particularly if antivirals are taken during the earlier stages of influenza infection 1 , 2 , 3 . A 2003 study suggests a 60% reduction in influenza hospitalization rates for patients who received early antiviral treatment for seasonal influenza 4 .…”
Section: Introductionmentioning
confidence: 99%